QUIET FIRING AND SILENT FIRING FROM THE PERSPECTIVE OF INDONESIAN LABOR LAW - Achmad Benyamin Daniel; Lia Christine; Catharina Dewi Wulansari (CV. RADJA PUBLIKA, 2025)
Quiet firing and silent firing are emerging phenomena in employment, arising alongside the transformation of industrial relations in the digital and platform economy era. Quiet firing refers to a company's strategy of encouraging employees to resign without formal termination, while silent firing occurs when employees are